1971
DOI: 10.1128/jb.106.1.51-57.1971
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Iron-Transport Compound Enterochelin: Mutants of Escherichia coli Unable to Synthesize 2,3-Dihydroxybenzoate

Abstract: Mutants of Escherichia coli K-12 blocked in each of the three enzymatic reactions between chorismate and 2,3-dihydroxybenzoate, in the pathway leading to the iron-sequestering compound enterochelin, have been isolated and biochemically characterized. The three genes concerned (designated entA, entB and entC ) have been shown to be clustered on the chromosome between purE and gal and to be loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Second, tonB mutants were isolated in a strain (RK1044) that carried an entA mutation. Young et al (25) had shown that entA mutants were specifically blocked in the pathway leading to the biosynthesis of enterochelin. When B12 transport was examined in entA tonB double mutants, the secondary phase of B,2 transport was still not detectable.…”
Section: Resultsmentioning
confidence: 99%
“…Second, tonB mutants were isolated in a strain (RK1044) that carried an entA mutation. Young et al (25) had shown that entA mutants were specifically blocked in the pathway leading to the biosynthesis of enterochelin. When B12 transport was examined in entA tonB double mutants, the secondary phase of B,2 transport was still not detectable.…”
Section: Resultsmentioning
confidence: 99%
“…Enterobactin synthetase activity was first analysed using chromatographic fractions obtained from cell extracts which, when combined, produced enterobactin from L-serine, ATP, and DHBA {Bryce and Brot, 1972). A series of enf mutants were isolated which defined the genes entA, entB, entC, entD, entE, entF, and entG, as well as a transport function gene, fep Woodrow ef al.. 1975;Young et al, 1971). Chromatographic fractions from iron-starved cells were mixed with extracts from the ent mutants to reoonstitute enterobactin synthetase activity (Greenwood and Luke, 1976;Greenwood and Luke, 1980;Woodrow ef al., 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The genes specifying enterobactin biosynthesis and transport functions map to minute 13 of the chromosome (Bachmann, 1983), and are expressed coordinately in response to the intracellular iron concentration (Fleming et al, 1983). Enterobactin biosynthesis begins with the conversion of chorismate, an intermediate of aromatic amino acid biosynthesis, to 2,3-dihydroxybenzoate (DHBA) by the activities encoded by entC, entB, and entA (Young et al, 1971). DHBA and L-serine are subsequently converted to enterobactin by the activities ascribed to EntD, EntE, EntF, and EntG Woodrowe^a/., 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Wang & Newton (1969) isolated a second mutant, Chr2, which is sensitive to Cr(III) and has an impaired iron uptake. This mutant lacks the complete system to synthesize 2,3-dihydroxybenzoylserine (DHBS), a strong iron chelator that is currently known to be at the basis of the structure of the siderophore enterochelin (Young et al, 1971). As observed for B/rlt, the mutant Chr2 also presented reversion of Cr(III) sensitivity to the wild-type phenotype when iron was added at a high level to the medium.…”
Section: Genes/proteins Involved In Iron Metabolismmentioning
confidence: 98%